Examining transport futures with scenario analysis and MCA - Hickman, R; Saxena, S; Banister, D; Ashiru, O (Elsevier, 2012)
Climate change is a global problem and across the world the transport sector is finding it difficult to break projected increases in carbon dioxide (CO2) emissions; there are very few contexts where deep reductions in transport CO2 emissions are being made. A number of research studies are now examining the potential for future lower CO2 emissions in the transport sector. This paper develops this work to consider some of the wider sustainability impacts (economic, social and local environmental) as well as the lower CO2 transport impacts of different policy trajectories. Hence the central argument made is for an integrated approach to transport policy making over the longer term – incorporating scenario analysis and multi-criteria assessment (MCA) – to help assess likely progress against a range of objectives., , The analysis is based on work carried out in Oxfordshire, UK. Different packages of measures are selected and two scenarios developed which satisfy lower CO2 aspirations, one of which also provides wider positive sustainability impacts. A simulation model has been produced to help explore the strategic policy choices and tensions evident for decision-makers involved in local transport planning. The paper argues for a ‘strategic conversation’ (Van der Heijden, 1996) at the sub-regional and city level, based upon future scenario analysis and MCA, discussing the priorities for intervention. Such an approach will help us examine the scale of change and trade-offs required in moving towards sustainable transport futures.